1998
DOI: 10.1037/0021-9010.83.3.377
|View full text |Cite
|
Sign up to set email alerts
|

Relating member ability and personality to work-team processes and team effectiveness.

Abstract: Six hundred fifty-two employees composing 51 work teams participated in a study examining relationships among team composition (ability and personality), team process (social cohesion), and team outcomes (team viability and team performance). Mean, variance, minimum, and maximum were 4 scoring methods used to operationalize the team composition variables to capture the team members' characteristics. With respect to composition variables, teams higher in general mental ability (GMA), conscientiousness, agreeabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

86
1,381
10
18

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,211 publications
(1,495 citation statements)
references
References 77 publications
86
1,381
10
18
Order By: Relevance
“…This result is in line with previous findings (Barrick, Stewart, Neubert;& Mount, 1998;Prati et al, 2003;Rapisarda, 2002). EI thus seems repeatedly to play a part in team cohesiveness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in line with previous findings (Barrick, Stewart, Neubert;& Mount, 1998;Prati et al, 2003;Rapisarda, 2002). EI thus seems repeatedly to play a part in team cohesiveness.…”
Section: Discussionsupporting
confidence: 93%
“…Would a group that is only composed of members with high-EI ratings always perform better than a mixed group? In addition to the mean score, it would be relevant to measure maximum and minimum EI scores along with team variance, following the example of Barrick, Stewart, Neubert, and Mount (1998) in their study on the impact of the personality at group level. Such an approach would allow answering these questions.…”
Section: Ei and Performancementioning
confidence: 99%
“…Meta-analyses examining the relationship between performance and the Big Five traits have demonstrated the significant impact personality can have on job performance at the individual level (Barrick & Mount, 1991;Tett, Jackson, & Rothstein, 1991). Additionally, new research has begun to extend this focus to team level performance as well (Mohammed & Angell, 2003;Neuman et al, 1999;Barrick et al, 1998;Barry & Stewart, 1997).…”
Section: Personalitymentioning
confidence: 99%
“…Some recent studies have examined the impact of team member personality diversity in terms on team performance. For example, Barrick et al (1998) examined a variety or organizational workteams. Correlation results from this study revealed less diversity in conscientiousness was related to better team performance; less diversity in agreeableness was related to greater cohesion, less conflict, greater communication, and greater workload sharing; and more diversity in extroversion related to more cohesion.…”
Section: The Impact Of Team Member Similarity/diversitymentioning
confidence: 99%
See 1 more Smart Citation